The Islamic College Scholarship of Future: From Educational Dualism to Integration of Science - Miftahul Huda; Rhoni Rodin (At-Ta'dib, 2021)
The dichotomy of education that has swept the Islamic world is recognized as having created split of Muslim personalities. Educational institutions produce experts who are qualified in spiritual-transcendental issues, but unable to face the objective reality of social life that demands attention to every change that occurs. On the other hand, experts born from the world of general education institutions are very smart in dealing with the realities of social life, experts in the fields of science technology, economics, politics, and so on. However, it is not uncommon for people to be completely dry, even devoid of spirituality, which causes their lives to be unsettling and at the same time detrimental to personal, family and community life. This study uses a qualitative approach, with a literature review method. The results show that the dichotomy of science is the separation between religious and general disciplines, which in turn gives birth to a new term called educational dualism, namely religious education and general education. The dichotomous view that separates the religious sciences and general sciences is contrary to the concept of Islamic teaching which has integralistic teachings. Islam teaches that the affairs of the world are not separate from the affairs of the hereafter. The implication is that when referring to Islamic teachings, general sciences should be understood as an inseparable part of the religious sciences. The Islamic Religious College (STAIN / IAIN / UIN) must have the courage to review the vision, mission, and scientific paradigm that it has built over the past few decades. The aim of STAIN / IAIN / UIN as a Religious Higher Education needs to be oriented towards the birth of a bachelor who has three abilities at once, namely the ability to analyze academically, the ability to innovate and the ability to lead according to the demands of social, scientific, and professional problems in one breath of ethos. scientific and religious.